Tandem Stance for Fall Prevention in Elderly with Type 2 Diabetes Mellitus : a Case Study - Irma Darmawati; Trisna Aulianti (Universitas Pendidikan Indonesia, 2022)
A Tandem Stance is a therapy for fall prevention in the elderly, especially with type 2 diabetes mellitus. People with diabetes mellitus have a risk of forming wounds that are difficult to heal if they have an accidental fall. The purpose of this study was to analyze the implementation of tandem stance therapy as fall prevention for the elderly with T2DM. The research design used an evaluative design is a case study with data analysis using descriptive-analytic. The case study was carried out on the elderly aged 62 years with diabetes mellitus. Tandem walking exercises are carried out for approximately 10-15 minutes and are carried out for 7 days. Evaluation on the 7th-day intervention showed that the client has been able to adjust the balance to stand, walking is normal, and the balance of the body, especially when walking has increased. The patient says she doesn't feel stiff in the joints, only sometimes feels achy and easily tired. It was concluded that tandem stance therapy is recommended for fall prevention in the elderly. Community nurses can implement this intervention to reduce the risk of falls in the elderly group.